Correction: Alternative Strategy for Development of Dielectric Calcium Copper Titanate-Based Electrolytes for Low-Temperature Solid Oxide Fuel Cells - Rauf, Sajid; Hanif, Muhammad Bilal; Tayyab, Zuhra; Veis, Matej; Shah, M. A. K. Yousaf; Mushtaq, Naveed; Medvedev, Dmitry; Tian, Yibin; Xia, Chen; Motola, Martin; Zhu, Bin (Nano-Micro Letters, 2026)
The development of low-temperature solid oxide fuel cells (LT-SOFCs) is of significant importance for realizing the widespread application of SOFCs. This has stimulated a substantial materials research effort in developing high oxide-ion conductivity in the electrolyte layer of SOFCs. In this context, for the first time, a dielectric material, CaCu3Ti4O12 (CCTO) is designed for LT-SOFCs electrolyte application in this study. Both individual CCTO and its heterostructure materials with a p-type Ni0.8Co0.15Al0.05LiO2−δ (NCAL) semiconductor are evaluated as alternative electrolytes in LT-SOFC at 450–550 °C. The single cell with the individual CCTO electrolyte exhibits a power output of approximately 263 mW cm−2 and an open-circuit voltage (OCV) of 0.95 V at 550 °C, while the cell with the CCTO–NCAL heterostructure electrolyte capably delivers an improved power output of approximately 605 mW cm−2 along with a higher OCV over 1.0 V, which indicates the introduction of high hole-conducting NCAL into the CCTO could enhance the cell performance rather than inducing any potential short-circuiting risk. It is found that these promising outcomes are due to the interplay of the dielectric material, its structure, and overall properties that led to improve electrochemical mechanism in CCTO–NCAL. Furthermore, density functional theory calculations provide the detailed information about the electronic and structural properties of the CCTO and NCAL and their heterostructure CCTO–NCAL. Our study thus provides a new approach for developing new advanced electrolytes for LT-SOFCs. Highlights: 1 Dielectric CaCu3Ti4O12 (CCTO) was used as electrolyte in low-temperature solid oxide fuel cells for the first time. 2 A new heterostructure electrolyte was designed based on CCTO and Ni0.8Co0.15Al0.05LiO2−δ (NCAL). Promising ionic conductivity and high fuel cell performance were achieved 3 CCTO–NCAL realized an electrolyte function due to its good dielectric property and a heterojunction effect.